Predicting severe alcohol use disorders in primary care using number of heavy drinking days. (25th July 2022) - Metz, Verena E.; Palzes, Vanessa A.; Kline‐Simon, Andrea H.; Chi, Felicia W.; Weisner, Constance M.; Sterling, Stacy A.
Abstract: Background and Aims: Although screening for unhealthy alcohol use is becoming more common, severe alcohol use disorders (AUDs) associated with the most severe medical and socio‐economic sequelae still often go unidentified in primary care. To improve identification of severe AUDs and aid clinical decision‐making, we aimed to identify a threshold of heavy drinking days (HDDs) associated with severe AUDs. Design, Setting and Cases: This cohort study analyzed electronic health record data of 138 765 adults who reported ≥ 1 HDD (4+ drinks/occasion for women and men aged ≥ 65 years, 5+ for men aged 18–64 years) during a 3‐month period at a routine alcohol screening in primary care in a large Northern California, USA health‐care system from 2014 to 2017. Our sample was 66.5% male, 59.7% white, 11.0% Asian/Pacific Islander, 5.0% black, 17.4% Latino/Hispanic and 7.0% other/unknown race/ethnicity; the mean age was 40.6 years (standard deviation = 15.2). Measurements: We compared sensitivity and specificity of different thresholds of the reported number of HDDs during a 3‐month period for predicting severe AUD diagnoses in the following year, in the full sample and by sex and age. Findings: The prevalence of severe AUD diagnoses in the year after the screening was 0.6%. The optimal threshold predicting future severe AUD diagnoses in the full sample was ≥ 5 HDDs during a 3‐month period [sensitivity = 68.9%, 95% confidence interval (CI) = 65.9, 72.0; specificity = 63.2%, 95% CI = 62.9, 63.4], but varied by sex and age. Women had a lower threshold than men (4 versus 6 HDDs), which decreased as women aged (from 5 HDDs among 18–24 years to 4 HDDs ≥ 25 years), but increased as men aged (from 5 HDDs among 18–24 years to 6 HDDs among 25–64 years, to 7 HDDs ≥ 65 years). Conclusions: Five or more heavy drinking days in a 3‐month period may indicate heightened risk of future severe alcohol use disorder in an adult primary care population. The optimal thresholds are lower for women than for men, and thresholds decrease as women age but increase as men age.